Two good dogs - Wilson, Susan, 1951- (St. Martin's Press, 2017)
"When Cody, a troubled fourteen-year-old, witnesses a murder, she tells no one. But it begins a spiral for her from which she cannot escape. Her worried mother Skye thinks a change of scene is just what her introverted, withdrawn daughter needs and since her dream has always been to own an inn, she jumps at the chance to buy a dilapidated bed & breakfast in the Berkshires. But being an innkeeper is harder than it seems and Cody still seems to fall in with the wrong crowd. When Adam March arrives as the inn's only guest, he is accompanied by his rescued pit bull, Chance, a dog who has saved Adam in more ways than one. Cody and Chance begin a wary bond and soon, Adam finds another rescue who needs the kind of attention he gave Chance years ago. With Adam and Skye beginning a tentative relationship and Chance showing Cody how to trust again, this new-found family seems to be on the brink of second chances. But soon, a murderer is closing in--someone hiding in plain sight, and threatening everything and everyone--even Cody's life"--